Sistem Pendukung Keputusan Dalam Pemilihan Pembimbing Skripsi Menggunakan Metode Profile Matching Di Program Studi PTIK Universitas Islam Negeri Sjech M.Djamil Djambek Bukittinggi - Abdul Aziz; Liza Efriyanti; Supratman Zakir; Jasmienti Jasmienti (Politeknik Negeri FakFak, 2024)
This research proposes the use of a decision support system based on the Profile Matching method to determine the thesis supervisor. This method is effective in making decisions that are in accordance with the concentration of the thesis title, functional position, and educational level of the lecturer. This research refers to the concept of a decision support system that offers several alternative choices to assist management in making decisions efficiently. The Profile Matching method is carried out with the stages of variable weighting, factor grouping, and total value calculation. This research also refers to related studies that have been conducted previously to build a more effective and efficient system in determining supervisors. The research method used is Research and Development with a waterfall System Development Life Cycle (SDLC) model. The results showed that the use of a decision support system with the Profile Matching method can provide recommendations for supervisors in accordance with the criteria set. Product testing using Aiken's V and ISO/IEC 25010 standards also shows that this system is feasible to use with good validity values and quality that meets standards. In conclusion, the decision support system with the Profile Matching method can help speed up and improve efficiency in determining thesis supervisors in the PTIK study program at UIN Sjech M.Djamil Djambek Bukittinggi. Suggestions for further development are to consider integration with web technology for ease of access and use.